Practices and Challenges of the Validity of Exploratory Factor Analysis (EFA)-Based Assessment Instruments: A Systematic Literature Review 2020–2025 - Mannan, Abd; Suparto, Suparto; Kusaeri, Kusaeri (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The validity of assessment instruments is the basis for ensuring the quality of learning assessment. A valid instrument allows the results of the evaluation to be used appropriately in educational decision-making. This study aims to examine the practice of using Exploratory Factor Analysis (EFA) and identify common weaknesses in the validation of assessment instruments through Systematic Literature Review (SLR) based on the PRISMA guidelines. Articles were searched from the Scopus database of 2020–2025, with 30 selected articles out of 746 analyzed. The results show that EFA is widely used to explore the validity of constructs in cognitive, affective, and psychomotor assessments in the fields of education, psychology, social, and Islamic Religious Education. The EFA is effective in identifying the structure of latent factors in instruments that do not yet have a standard theoretical model. Some common challenges include difficulty determining the number of factors, confusion between EFA and PCA, and limitations in dealing with residual correlations. Recommended solutions include parallel analysis, fit indices, the use of ESEM, as well as improved methodological training. This study concludes that the appropriate use of EFA supports the development of instruments that are more valid and adaptive to the needs of today's educational assessments.